Closed Loop Analysis of Multilevel Inverter fed Drives - Bharath VS; Gopinath Mani (Institute of Advanced Engineering and Science, 2014)
This paper deals with the simulation and implementation of multilevel inverter for drives application. Here the focuses will be on improving the efficiency of the multilevel inverter and quality of output voltage waveform. The circuit is developed towards high efficiency, high performance, and low cost, simple control scheme. Harmonics Elimination were implemented to reduce the Total Harmonics Distortion (THD) value which is achieved by selecting appropriate switching angles. In this paper to determine the performance of rectifier, steady state analysis is done. Furthermore, the merits of multilevel inverter topology are inherited.Closed loop control is done to analysis the stability of the system.DOI: http://dx.doi.org/10.11591/ijpeds.v4i3.5937